Pengaruh Literasi Keuangan, Modal Kerja dan Inovasi Digital terhadap Sustainability Finance Performance pada UMKM Fashion di Kota Surakarta - Sevina Aira Ayu Maria Pawestri; Naili Amalia (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Although fashion SMEs in Surakarta play an important role in the local economy, they still face challenges in financial management and sustainability. This study examines the effects of financial literacy, working capital, and digital innovation on sustainable financial performance. Survey data from 100 respondents were analyzed using multiple regression. The results show that financial literacy and digital innovation significantly influence sustainable financial performance, while working capital does not. These findings emphasize the importance of improving financial literacy and digital adoption to support SME sustainability. Enhancing financial literacy equips SME owners with the necessary skills to make informed financial decisions, while digital innovation allows them to streamline operations and reach a broader market. The lack of significant impact from working capital suggests that factors beyond financial resources, such as knowledge and technology, are crucial for long-term sustainability. The study highlights the need for policy interventions and programs that focus on increasing financial literacy and encouraging digital transformation in SMEs to ensure their growth and resilience in the competitive market.